Is the practice of autonomy support the missing element in teacher training at university? A study on the effects of an intervention based on self-determination theory on biology preservice teachers’ knowledge, beliefs, and intentions - Großmann, Nadine; Fries, Stefan; Wilde, Matthias (Frontiers in Psychology, 2023)
Teacher education at universities often lacks practice although preservice teachers should be equipped with effective teaching methods. We conducted an intervention to convey and practice autonomy-supportive teaching behavior (ASTB) with 63 preservice teachers. The first control group (n=76) did not receive any information on ASTB. A second control group (n=54) had their regular seminar on ASTB without practicing what they had learned. Significant differences in the participants' (Mage = 24.18 ± 3.26 years; Msemester = 7.61 ± 1.84; 63% female) knowledge, beliefs, and intentions were found. Participants of the intervention had higher theoretical and practical knowledge regarding ASTB and a higher level of perception that ASTB is easy to implement than a seminar without information on ASTB (first control group) and the regular seminar (second control group). That is, their knowledge acquisition and their belief about the ease of implementation were positively affected by the intervention in comparison to both control groups. Although no significant differences were found, preservice teachers in the intervention group also showed the highest level of agreement with the belief about the effectiveness of ASTB and the most pronounced intentions to implement ASTB. The results of our study show that the developed intervention based on SDT had a positive impact on preservice teachers' knowledge and beliefs about ASTB as well as their intention to apply it in the future. Since teacher education at university often lacks practice, the development of such effective theory-and practice-based interventions for preservice teachers is especially important. The practical skills acquired in our study are of particular importance for one central challenge teachers face in their profession: the need to counteract the decreasing trend of student motivation during secondary schooling.